The impact of mineral resources on foreign direct investment in the Southern African development community: a panel data analysis - Nyangoni, Kudzai Kudziyamira (My University, 2020)
This study analyses the impact of mineral resources on Foreign Direct Investment (FDI) flows to the Southern African Development Community (SADC) region. Absence of studies linking FDI to mineral resource endowment prompted this study. Therefore, the purpose of this study is firstly, to establish whether mineral resource endowment influences foreign direct investment flows to the SADC region and secondly, to establish the extent to which government institutions improve the impact of mineral resource endowment on FDI flows to the SADC region. The study employs use of generalized methods of moments (GMM) estimation technique to test the impact on FDI of various factors identified by existing literature as having effect on FDI flows. The study suggests that in addition to natural resource endowment, other factors included in the model do influence the movement of FDI. The level of political and legal instability experienced in the SADC region negatively affects FDI inflows. This result infers that SADC member countries should review their legal and political infrastructures so as to attract FDI into their countries. High Inflation rates in SADC region also negatively affect FDI flows to the region. Therefore, in addition to political and legal instability, economic instability in SADC member countries may also deter foreign investors from investing in SADC region. The results also show that trade openness and GDP growth have significant effect on FDI flows into the region. Other than mineral resource endowment, all other factors are within the control of SADC state governments. Instituting the right policies can go a long way in creating the right environment to attract FDI flows to the SADC region. The results of the study may not be applicable to SADC member countries only. Therefore, a research with a larger sample of African countries might reveal more interesting features.
A research report submitted in fulfilment of the requirements for the degree of Masters of Management in Finance and Investment (MMFI) to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2020
Keywords: Foreign Direct Investment; Southern African Development Community; Mineral resources; SDG-8: Decent work and economic growth